Effects of Central Obesity on Esophageal Epithelial Barrier Function - Gibbens, Ying Y.; Lansing, Ramona; Johnson, Michele L.; Blevins, Christopher H.; Katzka, David A.; Iyer, Prasad G. (The American journal of gastroenterology, 2021)
We assessed if obesity perturbs the esophageal epithelial barrier function independent of promotion of gastroesophageal reflux (GER). Thirty-eight participants were divided into 4 groups: Obesity-/GER-, Obesity+/GER-, Obesity-/GER+, and Obesity+/GER+. Esophageal intercellular space and desmosome density (structural integrity) and fluorescein leak (functional integrity) were measured. The Obesity+/GER- group demonstrated increased intercellular space, reduced desmosome density, and increased fluorescein leak compared with control subjects. These changes were similar but not additive to findings seen in Obesity-/GER + and Obesity+/GER+ patients. Central obesity impairs structural and functional integrity of the esophageal barrier independent of GER, likely predisposing to esophageal injury.